In Search of Legal Foundation for Indonesian Family Firms - Dewi, Yetty Komalasari (UI Scholars Hub, 2016)
One of the factors that affect Indonesia’s economic growth is the existence of business firms. Most business firms in Indonesia are in the form of family-owned firm, and they are considered to constitute the backbone of the economic development. Family firms represent the most enduring business model in the world. The continuing success of family firms through the generations relies on ensuring the next generation. However, the issue of family firms is rarely discussed in particular from the perspective of corporate law. In fact, from legal perspectives, there are some issues dealing with this type of firm, among other, the lack of an overall definition of the term “family business”. It is because family businesses and small medium enterprises (SMEs) are widely understood synonymously in spite of the fact that they exist in every size class. Other issue is the question of its legal basis or legal framework in terms of its corporate governance. Many Indonesian business players lack the basic understanding of corporate law. It is partly because obligations set out in the corporate law are incompatible with the values and cultures in Indonesia where “kinship principle” is deeply rooted. This article aims to describe the characteristics and the legal frameworks for family firms in Indonesia. It also recommends the government to take progressive measures by providing clear regulations on family firms in Indonesia. This will reinforce family firms’ contribution to economic development of Indonesia in the future.